2008
DOI: 10.1158/1535-7163.mct-07-2222
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D3 analogue EB1089 inhibits the proliferation of human laryngeal squamous carcinoma cells via p57

Abstract: The objective of this study is to evaluate the role of the cyclin-dependent kinase inhibitor p57 in EB1089-inhibited proliferation of human laryngeal squamous carcinoma cells (HEp-2). HEp-2 cells were treated with the vitamin D 3 analogue EB1089 for 48 h and total RNA was extracted for reverse transcription-PCR amplification using primers for the p57 coding sequence. Proteins were detected by Western blot analysis. For interference using silencing RNA (siRNA), HEp-2 cells were transfected with siRNA specific f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…In particular, immunoblot analysis showed that EB1089 inhibited the secretion of IGF-2 and stimulated the production IGFBP-6. More recently Lu et al (2008) reported that EB1089 inhibits the proliferation of Hep-2 human laryngeal squamous carcinoma cells. The growthinhibiting activity of this molecule appeared to be due to an increase of p57 cyclin-dependent kinase inhibitor at mRNA and protein levels induced by this molecule.…”
Section: Eb1089 (Seocalcitol)mentioning
confidence: 99%
“…In particular, immunoblot analysis showed that EB1089 inhibited the secretion of IGF-2 and stimulated the production IGFBP-6. More recently Lu et al (2008) reported that EB1089 inhibits the proliferation of Hep-2 human laryngeal squamous carcinoma cells. The growthinhibiting activity of this molecule appeared to be due to an increase of p57 cyclin-dependent kinase inhibitor at mRNA and protein levels induced by this molecule.…”
Section: Eb1089 (Seocalcitol)mentioning
confidence: 99%
“…It has been reported that a vitamin D3 analog, EB1089, inhibits the proliferation of human laryngeal squamous carcinoma cells by inducing the accumulation of p57 Kip2 . Of interest, the molecule is about 60-fold more potent than vitamin D3 and does not show significant hypercalcemic effects (153). In addition, zoledronic acid, a bisphosphonate molecule endowed with interesting antiproliferative activity, has been reported to increase the level of p57 Kip2 in leukemic cell lines (154).…”
Section: Cdkn1c Targeting and Cancer Treatmentmentioning
confidence: 99%
“…Vitamin D analogs inhibit proliferation of human laryngeal squamous carcinoma cells 18 . Lipworth et al 19 observed a negative correlation between dietary intake of vitamin D and risk of squamous cell carcinoma of the esophagus and oral or pharyngeal cancer.…”
Section: Discussionmentioning
confidence: 99%